Power and Pay: The Union and Equal Pay at B.C. Electric/Hydro - Creese, Gillian (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1993)
This paper examines the struggle for equal pay for women in a large office union composed of female clerical and male technical and manual workers. The Office and Technical Employees' Union pursued "equal pay for equal job evaluation" for over 30 years from 1949 to 1981, while the employer, B.C. Electric/Hydro, systematically restructured unequal pay. At the same time, union negotiating practices and priorities also reinforced the gendered hierarchy in the workplace, and equal pay for women remained a sectoral 'women's issue' rather than a core general union issue.